Using Multimodal Analgesia for Breakthrough Pain in Stage IV Breast Cancer Patient - Wijaya, Indriyani; Mahmud (Indonesian Journal of Anesthesiology and Reanimation, 2023)
Introduction: Breakthrough Pain (BTP) is experienced as mild to moderate-severe pain, from only a few seconds to hours. It causes a decrease in the quality of life and functional capacities. Furthermore, BPT must be recognizable, assessed, and controlled to prevent its relapse and severity. Case report: A woman, 45 years old, having breast cancer along with pulmonary, femur, and cervical metastases, came with the main complaint of pain. The patient had a pain score of NRS 9, which was felt intermittently for the last 3 months. Treatment has been carried out with MST 10 mg/8 hours and a Durogesic® patch (fentanyl 50 mcg/h) but the pain did not subside. Moreover, the patient was unable to identify any precipitating factors or pain relievers, while the diagnosis confirmed BTP. The rescue dose was administered in a range of 10 – 20% of the total daily dose in the last 24 hours equivalent to 11 – 22 mg intravenous Morphine or equianalgesic with 110 – 220 mcg of fentanyl. For immediate effect, transmucosal fentanyl was recommended, but this preparation is currently unavailable. Moreover, therapy was carried out with the continuous administration of Morphine, and the pain reduced to NRS 0 – 3 on the second day. Conclusion: Transmucosal fentanyl, either buccal, sublingual, oral, or nasal mucosa, was proven to be effective in treating BTP. However, when transmucosal fentanyl is not available, multimodal analgesia is an effective alternative.